Market facts about the Spokane country.
"The purpose of this booklet is to place before executives of manufacturers and advertising agencies information of real value in planning sales and advertising campaigns for the prosperous, rapidly growing Pacific Northwest; and to aid salesmen in securing or extending distribution"--Foreword.